Carcinoid heart disease - Stephen A. Geller; Fernando Peixoto Ferraz de Campos (University of São Paulo, 2013)
The images are of the tricuspid valve and the pulmonic valve from the autopsy of a patient with mid-gut neuroendocrine carcinoma, carcinoid pattern, extensively metastatic to the liver. The patient had typical "carcinoid syndrome," including clinical evidence of tricuspid and pulmonic stenosis and insufficiency. The tricuspid valve (left) shows slight retraction and distortion by the overlying endothelial deposition of plaque composed of acid mucopolysaccharide-rich matrix with varying amounts of smooth muscle cells and collagen fibers. The plaque material causes partial coalescence of chordae tendinae with effacement of the usual delicate strands. The pulmonic valve (right) shows more marked distortion with shrinkage and obliteration of cusps and coalescence at the commissures. Beneath the plaque the valves are intact.